Effects of fill modes on N2O emission from the SBR treating domestic wastewater - Park, KY; Lee, JW; Inamori, Y; Mizuochi, M; Ahn, KH (I W A PUBLISHING, 2001)
Nitrous oxide (N2O) gas is emitted as an intermediate in the biological nitrogen removal process. A track study was performed to investigate the characteristics of N2O emission depending on the cyclic mode oia sequencing batch reactor (SBR). A major emission of N2O took place at the aerobic phase, while N2O emission at the anoxic phase was insignificant. Especially, the highest N2O emission rate was observed at the initial stage of aerobic phase under the limited dissolved oxygen (DO) condition. Under such a condition, nitrite (NO2-) was transiently accumulated along with significant N2O emission due to incomplete nitrification. In addition, N2O production at the aerobic phase was strongly related with incomplete denitrification by nitrifiers. N2O emission could be reduced by change in fill modes in the SBR. A significant conversion to N2O took place in the SBR with the anoxic fill mode, while only small amount of N2O was conversed in the SBR with the aerobic fill mode, Relatively high concentration of ammonia nitrogen (NH4+) accelerated N2O production at the aerobic phase in the SBR with the anoxic fill compared to the aerobic fill. For control of N2O emission in the SBR, the aerobic fill mode could be an effective method even if denitrification efficiency may be reduced at the anoxic phase.
Keywords: NITROUS-OXIDE GAS; ACTIVATED-SLUDGE; WATER TREATMENT